MULTIMEDIA APPLICATIONS ON THE APPLICATION OF THE SEVEN WONDERS OF THE WORLD'S INFORMATION BY USING MACROMEDIA FLASH MX - Imron Maulana; Yudi Irawan Chandra, SKom., MMSI (Jurnal Sistem Informasi, 2005)
Multimedia application programs on the seven wonders of the world was createdusing Macromedia Flash MX program whose purpose is to create a computerapplication program that explains and introduces the seven wonders of the world intoa menu that can be opened by anyone who is interested and also want to learn orunderstand from the history of the seven wonders world. From here we just open ourhome page and then press the next button and then goes to area seven wonders of theworld and here we just choose to see the seven wonders of the world.Actionscript Libraries and other usage of this program is a facility that has beenprovided by Macromedia Flash MX to facilitate the manufacture andorganizationed.file- movie files required in the manufacture of the seven wonders ofthe world.